Utilization of Public Health Service Increased Risk Donors Yields Equivalent Outcomes in Liver Transplantation - V. A. Fleetwood; J. Lusciks; J. Poirier; M. Hertl; E. Y. Chan (Journal of Transplantation)
Background. The PHS increased risk donor (IRD) is underutilized in liver transplantation. We aimed to examine the posttransplant outcomes in recipients of increased-risk organs. Methods. We analyzed 228,040 transplants in the Organ Procurement and Transplantation Network database from 2004 to 2013. Endpoints were graft failure and death. Results were controlled for demographics and comorbidities. Statistical analysis utilized Fisher’s test and logistic regression. Results. 58,816 patients were identified (5,534 IRD, 53,282 non-IRD). IRDs were more frequently male (69.2% versus 58.3%, p<0.001), younger (34 versus 39, p<0.001), and less likely to have comorbidities (p<0.001). Waitlist time was longer for IRD graft recipients (254 versus 238 days, p<0.001). All outcomes were better in the IRD group. Graft failure (23.6 versus 27.3%, p<0.001) and mortality (20.4 versus 22.3%, p=0.001) were decreased in IRD graft recipients. However, in multivariate analysis, IRD status was not a significant indicator of outcomes. Conclusion. This is the first study to describe IRD demographics in liver transplantation. Outcomes are improved in IRD organ recipients; however, controlling for donor and recipient comorbidities, ischemia time, and MELD score, the differences lose significance. In multivariate analysis, use of IRD organs is noninferior, with similar graft failure and mortality despite the infectious risk.